Symposium on Spatial User Interaction 2019
DOI: 10.1145/3357251.3357590
|View full text |Cite
|
Sign up to set email alerts
|

LIVE: the Human Role in Learning in Immersive Virtual Environments

Abstract: This work studies the role of a human instructor within an immersive VR lesson. Our system allows the instructor to perform "contact teaching" by demonstrating concepts through interaction with the environment, and the student to experiment with interaction prompts. We conducted a between-subjects user study with two groups of students: one experienced the VR lesson while immersed together with an instructor; the other experienced the same contents demonstrated through animation sequences simulating the action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The latter work has used head movements as a proxy for visual attention and found that head movements shift between target and interaction partner. This finding partly supports the finding of [58] that the learners' engagement increases when a virtual instructor is presented. However, both works lack eye movement measurements.…”
Section: Related Worksupporting
confidence: 86%
See 1 more Smart Citation
“…The latter work has used head movements as a proxy for visual attention and found that head movements shift between target and interaction partner. This finding partly supports the finding of [58] that the learners' engagement increases when a virtual instructor is presented. However, both works lack eye movement measurements.…”
Section: Related Worksupporting
confidence: 86%
“…In addition to virtual peer-learners, the presence of virtual instructors may also have an impact on learning in VR. [58] investigated this and reports that learners engaged more with the environment and progressed further with the interaction prompts when a virtual instructor was provided. These works and findings indicate that the styles and types of virtual agents in the virtual environments may have several effects on students' attention and perception during immersion and should be taken into account.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, due to the constraints imposed by the COVID-19 pandemics, the use of VR for training and learning has receiving more attention and the influence of aspects such as users' visual attention and behavior are being explored. Simeone et al [26] found that the presence of a virtual instructor increases the engagement and accelerate the progress of the user during a learning experience. Bozkir et al [27] focused in three different objects-of-interest for measuring attention: peer-learners, instructor, and lecture material.…”
Section: Bowman and Mcmahanmentioning
confidence: 99%
“…Therefore, learning in senior universities, for example., may be organized differently from work-related education (Formosa, 2019). Crucially, VR/AR technology can disconnect learning from physical environments, establish new forms of learning assistance via VR-based lessons, and include gamification elements (Daniela and Lytras, 2019;Simeone et al, 2019;Yoshimura and Borst, 2020). • Health: The use of VR and AR in health promotion, such as psychotherapy and rehabilitation, can help to maintain health and well-being in older adults.…”
Section: Potentials Of Virtual Reality and Augmented Reality For Older Adultsmentioning
confidence: 99%